2019
DOI: 10.1159/000504327
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Upper Endoscopic and Endoscopic Ultrasound Features in the Differential Diagnosis of Gastrointestinal Stromal Tumors and Leiomyomas in the Upper Gastrointestinal Tract

Abstract: Background: Differentiation between benign and malignant subepithelial lesions (SELs) in the upper gastrointestinal tract (UGT) leads to far-reaching clinical consequences. An accurate diagnosis can be challenging because of the insufficient diagnostic yield of upper endoscopy, endoscopic ultrasound (EUS), and different types of biopsy. Aim: Our aim was to reveal the efficacy of upper endoscopic and EUS features for the differential diagnosis of hypoechogenic SELs (gastrointestinal stromal tumors [GISTs] and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The round shape and irregular margin of the lesion are also endoscopic ultrasonography features suggestive of GISTs. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The round shape and irregular margin of the lesion are also endoscopic ultrasonography features suggestive of GISTs. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…The round shape and irregular margin of the lesion are also endoscopic ultrasonography features suggestive of GISTs. [16] In the present study, we incorporated CT features of positive contrast enhancement and intra-tumoral necrosis and an endoscopic ultrasonography feature of uneven echogenicity as items for the scoring system, as statistically significant differences were observed in these features between GISTs and non-GISTs. Although it may be possible to increase the accuracy of our scoring system by adding other features characteristic of GISTs, this concept requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our EUS-AI model, we collected the normal B-mode images, and evaluation of the brightness or grayscale histogram, heterogeneity, shape, "halo" sign, and cystic changes in EUS images may help distinguish SELs. [16][17][18] However, there are other techniques that aid in the differentiation of SELs. A previous study demonstrated the usefulness of elastography in differentiating GISTs and non-GISTs, as the former were found to be harder.…”
Section: Discussionmentioning
confidence: 99%
“…A study was conducted about EUS reliabity for gastric sub epithelial lesions. Using histopathology as the gold standard, the overall diagnostic accuracy of EUS imaging was 49% (Vaicekauskas et al, 2020).…”
Section: Vol 27 No 2 April 2024 Flow Chart For Eus and Pathologic Dia...mentioning
confidence: 99%